George Washington : our first president - Jackson, Garnet; Van Wright, Cornelius; Hu, Ying-Hwa (New York : Scholastic, 2000)
A simple biography of George Washington, the first president of the United States.
K
"Cartwheel books."
600
K
Keywords: Presidents -- United States -- Biography -- Juvenile literature; Presidents